2016
DOI: 10.1007/s12288-016-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Philadelphia Positive Acute Myeloid Leukemia with Extensive Basophilia: A Diagnostic Dilemma

Abstract: Basophilia in peripheral blood as well as bone marrow is an unusual finding, seen in certain reactive and neoplastic conditions. Amongst the malignant hematological diseases, it is a diagnostic hall mark of chronic myeloproliferative disorders, particularly, chronic myeloid leukemia. Basophilia may also be seen in cases acute myeloid leukemia, particularly FAB AML M2 and M4. Here we document an interesting case of de novo acute myeloid leukemia which had extensive peripheral blood and bone marrow basophilia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A short duration of disease, absence of a prior history of chronic myeloid leukemia, no splenomegaly, and an absence of the Philadelphia chromosome/BCR-ABL fusion gene favored the diagnosis of a de novo AML-MRC over CML-MBC. The blasts with primary differentiation in ABL express CD9, CD13, CD33, CD22, CD36, CD123, CD34, HLA-DR and CD25 [3]. The current case showed a population of obvious mature basophils in morphology in bone marrow and peripheral blood smears, expressing CD11b, CD13 and CD123 along with myeloblasts, and indicated no expression of CD34, thus supporting a diagnosis of AML-MRC with basophilia over ABL.…”
mentioning
confidence: 48%
“…A short duration of disease, absence of a prior history of chronic myeloid leukemia, no splenomegaly, and an absence of the Philadelphia chromosome/BCR-ABL fusion gene favored the diagnosis of a de novo AML-MRC over CML-MBC. The blasts with primary differentiation in ABL express CD9, CD13, CD33, CD22, CD36, CD123, CD34, HLA-DR and CD25 [3]. The current case showed a population of obvious mature basophils in morphology in bone marrow and peripheral blood smears, expressing CD11b, CD13 and CD123 along with myeloblasts, and indicated no expression of CD34, thus supporting a diagnosis of AML-MRC with basophilia over ABL.…”
mentioning
confidence: 48%
“…There was higher chance of harboring Philadelphia chromosome in AML patients with splenomegaly and normal platelet count. Thus, cytogenetics testing should be emphasized in these patient subgroups as they have different treatment and poorer outcomes [25][26][27][28][29]. This study clearly demonstrated that the outcomes of APL patients were significantly better than non-APL AML.…”
Section: Discussionmentioning
confidence: 85%